Impact of Social Media on Mental Health - Jasleen Kaur (Journal of Advanced Research in Journalism & Mass Communication, 2025)
In recent years, social media has become a dominant force in shaping how individuals interact, communicate, and engage with the world. While it offers a lot of benefits, such as increased connectivity and access to information, its impact on mental health has raised concerns. This paper explores the various ways that social media is affecting mental well-being, focusing on both the positive and negative consequences. On the one hand, social media provides platforms for social support, self-expression, and community building. On the other hand, it has been linked to issues such as anxiety, depression, and feelings of isolation, especially among young people. Things like online bullying, comparing ourselves to others, and feeling the need to show a perfect life on social media can lead to mental health problems. This paper also examines existing research and studies to assess the extent of social media's impact on mental health and offers recommendations for mitigating its negative effects while promoting healthier usage patterns. By understanding how social media affects us, people and communities can work towards creating a healthier and more positive online space.